Negosiasi Makna Praktik Tarot dalam Kehidupan Religius Masyarakat Hindu di Kecamatan Buleleng - Ni Luh Putu Ayu Rantauyani; Ida Bagus Wika Krishna; I Nyoman Suka Ardiyasa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of modernity has not only transformed patterns of social life, but has also given rise to increasingly personal forms of reflective spirituality, one of which is tarot practice. In the context of Hindu communities in Buleleng District, this practice is significant because it emerges within a strong local religious system and gives rise to processes of acceptance, restriction, and reinterpretation. This study aims to analyze the meaning of tarot as a medium of self-reflection and to explain how that meaning is negotiated within the religious life of Hindu communities. This study employs a qualitative approach with a social phenomenology perspective. Data were collected through in-depth interviews, observation, and documentation involving nine informants, and were then analyzed thematically and interpretatively. The findings show that tarot is not understood as a substitute for religion nor as a source of absolute spiritual authority, but rather as a reflective medium for understanding inner conditions, life experiences, and considerations in decision-making. Acceptance of tarot occurs selectively through the negotiation of meaning between individuals’ subjective experiences, religious normative boundaries, and the social legitimacy operating within the community. These findings affirm that contemporary Hindu religiosity is adaptive toward new reflective practices as long as they do not displace religion as the primary framework of spiritual life.